Eliminating the need for fasting with oral administration of bisphosphonates. - Pazianas, M; Abrahamsen, B; Ferrari, S; Russell, R (2013)
Bisphosphonates are the major treatment of choice for osteoporosis, given that they are attached preferentially by bone and significantly reduce the risk of fractures. Oral bisphosphonates are poorly absorbed (usually less than 1% for nitrogen-containing bisphosphonates) and when taken with food or beverages create complexes that cannot be absorbed. For this reason, they must be taken on an empty stomach, and a period of up to 2 hours must elapse before the consumption of any food or drink other than plain water. This routine is not only inconvenient but can lead to discontinuation of treatment, and when mistakenly taken with food, may result in misdiagnosis of resistance to or failure of treatment. The development of an enteric-coated delayed-release formulation of risedronate with the addition of the calcium chelator, ethylenediaminetetraacetic acid (EDTA), a widely used food stabilizer, eliminates the need for fasting without affecting the bioavailability of risedronate or its efficacy.